DEEP-SEATED ULTRAPOTASSIC LIQUIDS - Perchuk L.L.; Yapaskurt V.O. (My University, 1998)
Analysis of experimental and natural data suggests that a pressure increase leads to an increase in the distribution coefficient of potassium between immiscible silicate and salt (carbonate or chloride) liquids, since the K2O concentration in the silicate melt decreases. In this case, the region of separation of the above liquids into layers becomes narrower and shifts to the region of alkali-poor melts, but the activity of K2O in the liquids remains extraordinarily high. As a result, K-clinopyroxene is the first to crystallize from a K-poor silicate liquid coexisting with a potassium carbonate (or chloride) melt. Analogs of such liquids are "fluid-melt" inclusions ((Si, Al) : (K, Na) : Ca = 7.7 : 10 : 4.4 (average)) in Zairian diamonds. Potassic pyroxenes from kimberlite nodules and diamonds may point to the existence of such water-bearing salt melts with up to 30 wt.% alkalies in deep mantle. The experimental data show that at P ≥ 70 kbar and T >1200°C, at equilibrium of chlorite and/or carbonate melts with pyroxene containing 1.2 wt.% K2O, the distribution coefficient of potassium is about 20. Such pyroxenes occur as microinclusions in garnets from some rocks of the diamondiferous Kumdy-Kol' deposit in the Kokchetav massif. It is suggested that K-pyroxene crystallized as a liquidus mineral from a K-poor silicate melt coexisting with a K-rich salt (KCl-K2CO3) liquid in the region of diamond stability.